Literary disco: Halid Ziya Uşaklıgil's intensive writing - Aydoğan, Yüce. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This study focuses on the literary texts of Halid Ziya Uşaklıgil in terms of the concept of intensity. Intensity as the experience of the breakdown of any psychic, perceptive and-spatial order constitutes the descriptive feature of the dramatic content level of Uşaklıgil's literary corpus. On the dramatic content level, the primary object of Uşaklıgil's literature is to textualize and to describe the experince of intensity. The concept of intensity has also a decisive importance concerning the fundamental features of the literary forms and the literary language that Uşaklıgil used. Ugakligil's literature, by exhibiting a literary manner aiming at subjectivizing, musicalizing and thus intensifying the literary language, comprises an intensive formal level. The literary language as it is conceived and practised by Uşaklıgil is not an informativelintentional language, but an intensive one. This study which focuses both on the dramatic content level and on the formal level of Uşaklıgil's literary production argues that both levels are constructed on the basis of the experince of intensity.